Pengaruh Kualitas Pelayanan, Kinerja Petugas dan Fasilitas terhadap tingkat Kepuasan Masyarakat dalam Pelaksanaan Program Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kecamatan Aur Birugo Tigo Baleh - Febriani, Dewi (CV. ITTC INDONESIA, 2022)
This study aims to analyze the effect of service quality, officer performance and facilities on the level of satisfaction in the implementation of PATEN in Aur Birugo Tigo Baleh District, Bukittinggi City. This study uses a quantitative approach because the observed symptoms are converted into numbers that are analyzed using statistics. The author chose the sample using a saturated sampling technique because the population is relatively small. So that the sample used in this study amounted to 63 people. The purpose of this study was to determine the effect of each variable of Service Quality (X1), Officer Performance (X2) and Facilities (X3) on Community Satisfaction (Y). (X1) Service Quality and (X2) Officer Performance have a significant and positive effect on Community Satisfaction and the Facility variable (X3) has a positive but not significant effect. It can be concluded that human resources and service quality are very important to be improved in order to create satisfaction for the people who get PATEN services. Keywords: Service Quality, Officer Performance, Facilities, Community Satisfaction, District integrated administrative services (PATEN)